Efektivitas Pengelolaan Sistem Informasi Manajemen Pendidikan (Emis) di Madrasah Aliyah Swasta YPP Sukamiskin Kota Bandung - Raden Syara Bisyara; Ara Hidayat (Departement of Mathematics Education, 2024)
Management Information System (MIS) comes with sophisticated technology to offer solutions to existing issues. MIS itself governs the utilization of human resources, technology, procedures, and data designed to generate information for an institution or organization. The research method employed in this study is Qualitative. Data collection techniques utilized include Observation Technique (observation), Interview Technique, Documentation Technique, and Triangulation technique. The management information system is actively and continuously developed. Each user of the management information system is entitled to provide positive inputs based on their needs. The management of the Private Islamic Senior High School (Madrasah Aliyah Swasta) YPP Sukamiskin in Bandung City is actively and continuously developed. The collection of Educational Management Information System (EMIS) faces obstacles such as prolonged time, the requirement of an unstable network/internet, and data duplication. The effectiveness of EMIS management at MAS YPP Sukamiskin in Bandung City can be measured through the speed and accuracy of the required data processing.